2013
DOI: 10.1289/ehp.1205784
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Human Hazard Characterization of Chemicals: A Tox21 Update

Abstract: Background: In 2008, the National Institute of Environmental Health Sciences/National Toxicology Program, the U.S. Environmental Protection Agency’s National Center for Computational Toxicology, and the National Human Genome Research Institute/National Institutes of Health Chemical Genomics Center entered into an agreement on “high throughput screening, toxicity pathway profiling, and biological interpretation of findings.” In 2010, the U.S. Food and Drug Administration (FDA) joined the collaboration, known in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
468
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 530 publications
(472 citation statements)
references
References 42 publications
0
468
0
4
Order By: Relevance
“…The Toxicology in the 21st Century (Tox21) is a unique collaboration among several US Federal Government partners created to develop a vision and devise an implementation strategy to shift the assessment of chemical hazards from traditional experimental animal toxicology studies to target-specific, mechanism-based biological observations largely obtained using in vitro assays [82]. In 2008, in response to the National Academy of Sciences' (NAS) report, Toxicity Testing in the 21st Century: A Vision and a Strategy [83], a collaboration was established between the National Institute of Environmental Health Sciences' (NIEHS) National Toxicology Program (NTP), the US Environmental Protection Agency's (EPA) National Center for Computational Toxicology (NCCT), and the National Human Genome Research Institute's (NHGRI) NIH Chemical Genomics Center (NCGC), presently part of the National Center for Advancing Translational Sciences (NCATS) [84].…”
Section: Toxicology In the 21st Centurymentioning
confidence: 99%
See 1 more Smart Citation
“…The Toxicology in the 21st Century (Tox21) is a unique collaboration among several US Federal Government partners created to develop a vision and devise an implementation strategy to shift the assessment of chemical hazards from traditional experimental animal toxicology studies to target-specific, mechanism-based biological observations largely obtained using in vitro assays [82]. In 2008, in response to the National Academy of Sciences' (NAS) report, Toxicity Testing in the 21st Century: A Vision and a Strategy [83], a collaboration was established between the National Institute of Environmental Health Sciences' (NIEHS) National Toxicology Program (NTP), the US Environmental Protection Agency's (EPA) National Center for Computational Toxicology (NCCT), and the National Human Genome Research Institute's (NHGRI) NIH Chemical Genomics Center (NCGC), presently part of the National Center for Advancing Translational Sciences (NCATS) [84].…”
Section: Toxicology In the 21st Centurymentioning
confidence: 99%
“…Efforts are underway to combine the use of iPSC models along with high-throughput screening assays using reporter gene assays [82], 3D organotypic cultures [94], human on a chip (www.ncats.nih.gov/research/reengineering/tissue-chip/ tissue-chip.html), and complementary animal models such as zebrafish [95,96] and C. elegans [97], and to incorporate human dosimetry and exposure to better predict toxicity across different organ systems [98]. As these multiple assay domains are being populated with data from the testing of chemicals, they are being anchored to relevant phenotypes from in vivo rodent and nonrodent animal studies as found in the EPA ToxRefDB [85,99], the NTP rodent database (CEBS) (www.niehs.nih.gov/research/resources/databases/ cebs), and whenever possible to the relevant phenotype in humans to develop better prediction models of toxicity.…”
Section: Toxicology In the 21st Centurymentioning
confidence: 99%
“…Especially considered for the future innovation of novel ENMs, safety evaluations should be integrated proactively and efficiently already in the material and product development phase [9,12]. Summarized under a concept termed 'Toxicity Testing in the 21st Century' or 'Tox21', biochemical and cell-based in vitro assays coupled with bioinformatics and modelling-driven in silico assays are now considered key to transforming toxicology from a previously animal-based testing practice into a computational science built on systems biology [2,4,6,[9][10][11]13]. The resulting novel research field is variably termed 'systems toxicology', 'toxicogenomics' or 'computational toxicology' [3,4,8,14,15].…”
mentioning
confidence: 99%
“…A constantly increasing number of chemicals and engineered nanomaterials (ENMs) emphasize the need of applying novel tools and screening technologies outside of the standard, both lengthy and expensive, rodent toxicological tests traditionally used in such work [1][2][3][4][5][6][7][8][9][10][11][12][13]. Especially considered for the future innovation of novel ENMs, safety evaluations should be integrated proactively and efficiently already in the material and product development phase [9,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation